2012
DOI: 10.1029/2012jg001962
|View full text |Cite
|
Sign up to set email alerts
|

Methane flux response to nitrogen amendment in an upland pine forest soil and riparian zone

Abstract: [1] Methane (CH 4 ) is an important anthropogenic greenhouse gas, up to 15% of which is consumed by terrestrial soils. In this field study of the CH 4 cycle of a pine forest, 18 plots were established at each of two sites, located 40 m apart. The upper site was well-drained and the lower site was poorly drained, but they shared similar overstory tree composition. Nitrogen was added as NH 4 , with greater variance than was observed at the upper site. High N treatments caused greater CH 4 release than the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 65 publications
0
8
0
3
Order By: Relevance
“… High and low refer to the variables in the column headers . does not include agricultural systems except tree plantations; NR indicates that there were no studies located reporting on the indicated effect in that ecosystem/biome; ND indicates those studies that found no difference in CH 4 flux with different values for that variable .1Adamsen and King, 1993; Borken and Beese, 2006,2Ambus and Christensen, 1995; van Huissteden et al, 2008,3Bowling et al, 2009; Koide et al, 2010,4Borken et al, 2003,5Sjogersten and Wookey, 2002; Borken et al, 2003,6McNamara et al, 2008,7West et al, 1999; Mariko et al, 2007,8Sjogersten and Wookey, 2002,9Menyailo et al, 2008,10Castro et al, 1994, 1995; Klemedtsson and Klemedtsson, 1997; Prieme et al, 1997; Butterbach-Bahl and Papen, 2002; McLain et al, 2002; Borken et al, 2006; Rosenkranz et al, 2006; Aronson et al, 2012,11Prieme et al, 1997; Groffman et al, 2006,12Castro et al, 1994; Bradford et al, 2000; Blankinship et al, 2010a; Xu and Luo, 2012,13Borken et al, 2006,14Castro et al, 1993; Hart, 2006,15Yavitt et al, 1990,16Born et al, 1990; Brumme and Borken, 1999,17Sitaula et al, 1995; Prieme et al, 1997; Kolb et al, 2005,18Neff et al, 1994; van den Pol-van Dasselaar et al, 1998,19Blankinship et al, 2010b,20Mosier et al, 1991; Torn and Harte, 1996; Mosier et al, 1997a,…”
Section: Environmental Factors and The Methane Cyclementioning
confidence: 99%
See 2 more Smart Citations
“… High and low refer to the variables in the column headers . does not include agricultural systems except tree plantations; NR indicates that there were no studies located reporting on the indicated effect in that ecosystem/biome; ND indicates those studies that found no difference in CH 4 flux with different values for that variable .1Adamsen and King, 1993; Borken and Beese, 2006,2Ambus and Christensen, 1995; van Huissteden et al, 2008,3Bowling et al, 2009; Koide et al, 2010,4Borken et al, 2003,5Sjogersten and Wookey, 2002; Borken et al, 2003,6McNamara et al, 2008,7West et al, 1999; Mariko et al, 2007,8Sjogersten and Wookey, 2002,9Menyailo et al, 2008,10Castro et al, 1994, 1995; Klemedtsson and Klemedtsson, 1997; Prieme et al, 1997; Butterbach-Bahl and Papen, 2002; McLain et al, 2002; Borken et al, 2006; Rosenkranz et al, 2006; Aronson et al, 2012,11Prieme et al, 1997; Groffman et al, 2006,12Castro et al, 1994; Bradford et al, 2000; Blankinship et al, 2010a; Xu and Luo, 2012,13Borken et al, 2006,14Castro et al, 1993; Hart, 2006,15Yavitt et al, 1990,16Born et al, 1990; Brumme and Borken, 1999,17Sitaula et al, 1995; Prieme et al, 1997; Kolb et al, 2005,18Neff et al, 1994; van den Pol-van Dasselaar et al, 1998,19Blankinship et al, 2010b,20Mosier et al, 1991; Torn and Harte, 1996; Mosier et al, 1997a,…”
Section: Environmental Factors and The Methane Cyclementioning
confidence: 99%
“…10Castro et al, 1994, 1995; Klemedtsson and Klemedtsson, 1997; Prieme et al, 1997; Butterbach-Bahl and Papen, 2002; McLain et al, 2002; Borken et al, 2006; Rosenkranz et al, 2006; Aronson et al, 2012,…”
Section: Environmental Factors and The Methane Cycleunclassified
See 1 more Smart Citation
“…In a temperate ecosystem, Aronson et al (2012) showed positive effects of soil water content (SWC) and N addition on soil CH 4 fluxes, but it is unsure whether such results will extrapolate to tropical forest ecosystems. Moreover, little is known about the capacity of soils to recover from one or multiple stressors, such as drought and changes in nutrient availability.…”
Section: Introductionmentioning
confidence: 99%
“…Itoh et al (2009) found that the soil moisture patterns could greatly affect seasonal and spatial variations in CH 4 fluxes within a temperate forest: during rainy summers, wetter sites exhibited large CH 4 emissions compared to dry areas, which were net sinks of CH 4 . Forest type, soil moisture, temperature, and pH have been shown to affect microbial communities involved in CH 4 production and oxidation; however, much remains unknown about methanogens and CH 4 -oxidizing bacteria in forests (Aronson et al, 2012). In past studies, CH 4 flux measurements in forests were conducted mainly using the chamber enclosure techniques due to the simplicity and relatively inexpensive nature of the method.…”
Section: Introductionmentioning
confidence: 99%